Economic aspects of protection and free trade - Uhl, Frank Edwin (My University, 1896)
Introduction: The voters of this country are steadily becoming better acquainted with economic problems. The study of them is becoming more common in our schools. This discussion in public is fairer than formerly; and papers and magazines are giving more space to such matters. The study of economics is being pursued from broader stand-points. As time passes now elements become allied with the old and require new solutions for the problems confronting society. There has indeed been great development in the general conception of economic problems, but improvement is still possible. There seems to be a general impression among the mess of voters that they should pay little attention to the intricacies of economic questions, and that they should follow leaders whose duty it is to study these things.
Citation: Uhl, Frank Edwin. Economic aspects of protection and free trade. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Economic problems; Schools; Society; Solutions; Theses; Manuscripts (documents)